Efektifitas Kemiringan Deflektor Kincir Air Savonius - Angga Andrian Kusdiat; Mohammad Alexin Putra (G-Tech: Jurnal Teknologi Terapan, 2023)
One of the renewable energy potentials that can be utilized is water energy. The performance of the wheel can also be improved, one of which is by applying Deflector. The waterwheel used is a Savonius type. In this study, deflector variations of 30°, 45°, and 60° were used. The water speed set is 0.8 m/s and 1 m/s. the performance increases. The best performance is on the deflector with an angle of 60°. The highest performance value is produced by the deflector at an angle of 60°, namely a maximum torque coefficient of 0.818, a maximum power coefficient of 0.817, and a maximum tip speed ratio of 2.448 obtained at a water speed of 0.8 m/s. The performance of wheel without a deflector produces a maximum torque efficiency of 0.4, a maximum power coefficient of 0.276, and a tip speed ratio of 1.79 at a water speed of 0.8 m/s.